Metagenomics: An Unbiased Tool for Understanding and Preventing Pandemics - Shakti Rath (مجله كليه طب الكندي)
Metagenomics is a branch of genomics that involves sequencing genetic material directly from environmental samples. Metagenomic data could facilitates evidence-based decisions while providing a more complete view of the microbial ecosystem in a pandemic setting. It would provide critical knowledge for future pandemic preparedness programs